2014
DOI: 10.1186/1179-5395-44-3
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effect of storage conditions on the natural drying of radiata pine logs for energy use

Abstract: Background: The effect of storage duration and technique on the moisture content of radiata pine (Pinus radiata D. Don) biomass logs in New Zealand was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…This was also observed by Visser et al (2014), for P. radiata logs, arguing that smaller diameter logs and split logs exhibit a larger surface area to mass ratio and a smaller distance water must move from the inner log to the surface in order to evaporate. Since wood-free water flows primarily along the stem evaporating form the log ends (Walker 2006), there must be a secondary movement across the stem if small diameter logs, large split logs and debarked logs dry faster than large whole logs (Abbot et al 1997, Visser et al 2014. Daily MC loss (ΔM) scaled positively following a power function with the MC at the beginning of the day (M), average air temperature (T) and the number of logs per square metre in the cross-section (N), and scaled negatively with air relative humidity (H).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This was also observed by Visser et al (2014), for P. radiata logs, arguing that smaller diameter logs and split logs exhibit a larger surface area to mass ratio and a smaller distance water must move from the inner log to the surface in order to evaporate. Since wood-free water flows primarily along the stem evaporating form the log ends (Walker 2006), there must be a secondary movement across the stem if small diameter logs, large split logs and debarked logs dry faster than large whole logs (Abbot et al 1997, Visser et al 2014. Daily MC loss (ΔM) scaled positively following a power function with the MC at the beginning of the day (M), average air temperature (T) and the number of logs per square metre in the cross-section (N), and scaled negatively with air relative humidity (H).…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, debarking would reduce drying times from 22 to 17 days in E. globulus and from 29 to 20 days in E. nitens to achieve a 20 % reduction in moisture content for piles freshly harvested/ stacked in January. Visser et al (2014) also found faster drying of debarked logs of P. radiata, suggesting that radial water movements are a significant contributor to the log drying process. Log lengths did not have a significant effect on moisture content loss in our study, although 244-cm logs dried on average 3 % faster than 350-cm logs.…”
Section: Discussionmentioning
confidence: 81%
“…In fact, both slope gradient and terrain ruggedness are somewhat moderate, which is the condition for effective pre-bunching. On steeper slopes, one may resort to winch-assist technology for pre-bunching, as it has already been done in other cases [35]. While terrain conditions would be suitable for the introduction of a complete winch-assist ground-based harvesting system, the need for minimizing soil impacts suggests sticking with the current grapple yarder system.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, timber harvesting on steep slopes has been achieved by manual felling with a chainsaw followed by extraction using specialized methods such as bladed skid trails, winching, or cable yarding [1,2]. Chainsaw felling and choker-cable setting tend to be more physically taxing and dangerous for workers [3], while the use of bladed skid trails, winching, and cable yarding can be impactful to the environment and/or have reduced efficiencies when compared with ground-based mechanized operations on less challenging terrain [1,2,4]. However, when mechanized operations demonstrated by Axelsson and Bell; when manual operations were replaced with mechanized operations, injury rates were reduced substantially [30,31].…”
Section: Introductionmentioning
confidence: 99%